Anion dependence of rabbit medullary collecting duct acidification. - Stone, D K (1983)
Rabbit medullary collecting duct (MCD) acidification has been demonstrated to occur by means of a sodium-independent, aldosterone-stimulated mechanism. We have examined the anionic dependence of this process by means of the isolated perfused tubule technique. Total replacement of perfusate chloride with gluconate enhanced tubular bicarbonate reabsorption (JHCO3), from a basal rate of 10.7 +/- 1.0 pmol X mm-1 X min-1 to a rate of 15.01 +/- 1.0 pmol X mm-1 X min-1. Removal of bath chloride, with and without removal of perfusate chloride completely abolished acidification. Bath, but not luminal 4-acetamido-4' isothiocyano-2,2'-disulfonic stilbene provoked a marked decrease in JHCO3 from 10.1 +/- 1.2 pmol X mm-1 X min-1 to 2.3 +/- 0.3 pmol X mm-1 X min-1. Measurement of chloride reabsorptive rate (JCl) revealed colinearity between JHCO3 (9.18 +/- 0.9 pmol X mm-1 X min-1) and JCl (9.75 +/- 1.18 pmol X mm-1 X min-1). We propose a model of mammalian distal nephron acidification in which (a) cellular base exit is effected by means of a basolateral membrane Cl-base exchanger and (b) net electroneutrality of electrogenic proton secretion is maintained by the parallel movement of an anionic species, functionally chloride.